Assessment of attributes influencing mode choice between formal and informal public transit services in Cartagena, Colombia (2020)
The ideal vision of offering sustainable urban transportation systems in cities worldwide, particularly in the Global South, is often hindered by the challenges posed by the operation of informal transportation services. Resulting in a scenario where the conception, design, and implementation of transportation policies and strategies is highly restricted by the notable adaptability of informal services. This research aims to understand and analyze the factors influencing users mode choice between formal and informal PuT alternatives in a Global South context, by means of a hybrid discrete choice (HDC) model. The HDC model includes not only traditional variables such as cost and time, but also the effects of a latent variable (perceived Quality of Service - QoS) through structural relations. In addition, we aim to identify similarities and differences among the perceptions of different population groups based on age, income and other sociodemographics. We discuss the practical implications of policies to manage informal...